Long Non-Coding NONRATG001910.2 Promotes the Proliferation of Rat Mesangial Cell Line HBZY-1 Through the miR-339-3p/CTNNB1 Axis - Gao, Jiarong; Zhu, Xiaoli; Chen, Hao; Jiang, Hui; Shi, Miaomiao; Wei, Liangbing; Qin, Xiujuan (Frontiers in Genetics, 2022)
Chronic glomerulonephritis (CGN) is one of the leading causes of end-stage renal disease (ESRD). A growing body of literature emphasizes the important role of long non-coding RNAs (lncRNAs) in the development and progression of the disease. However, the function of NONRATG001910.2 in the development of CGN was not well understood. This research aimed to investigate the effect of NONRATG001910.2 on CGN and revealed its potential molecular mechanisms. In this work, the expression of NONRATG001910.2 was detected by quantitative real-time polymerase chain reaction (qRT-RCR) in cell lines. We found that NONRATG001910.2 was significantly up-regulated in lipopolysaccharide (LPS) induced cells. High NONRATG001910.2 levels were associated with the development of CGN. In addition, NONRATG001910.2 knockdown inhibited cell proliferation and cell cycle. At the same time, we found that up-regulation of microRNA-339-3p (miR-339-3p) abrogated the biological roles of NONRATG001910.2 up-regulation. Moreover, the knockdown of CTNNB1 can upregulate miR-339-3p expression, thereby inhibiting cell proliferation. In conclusion, these results demonstrated that NONRATG001910.2 in LPS-stimulated rat mesangial cell line HBZY-1 (HBZY-1) by targeting miR-339-3p, which subsequently promotes the expression of CTNNB1, and suggested that NONRATG001910.2 may be a potential biomarker.